Cochrane review on 'Statins for the treatment of dementia'1. (2nd April 2012) - McGuinness, Bernadette; O'Hare, John; Craig, David; Bullock, Roger; Malouf, Reem; Passmore, Peter
<x xml:space="preserve">Abstract</x> Objectives This review aimed to assess the clinical efficacy and tolerability of statins in the treatment of dementia. Methods We searched the Specialized Register of the Cochrane Dementia and Cognitive Improvement Group, The Cochrane Library, MEDLINE, EMBASE, PsycINFO, CINAHL and LILACS, as well as many trials registries and grey literature sources (27 October 2008). Double‐blind, randomized controlled trials of statins given for at least 6 months in people with a diagnosis of dementia were included. Two independent authors extracted and assessed data independently against the inclusion criteria. Data were pooled where appropriate and entered into a meta‐analysis. Results Three studies were identified (748 participants, age range 50–90 years). All patients had a diagnosis of probable or possible Alzheimer's disease according to standard criteria, and most patients were established on a cholinesterase inhibitor. Change in Alzheimer's Disease Assessment Scale cognitive subscale from baseline was a primary outcome in three studies; when data were pooled, statins did not provide any beneficial effect in this cognitive measure (mean difference −1.12; 95% confidence interval −3.99, 1.75; p = 0.44). All studies provided a change in Mini‐Mental State Examination from baseline; there was no significant benefit from statins in this cognitive measure when the data were pooled (mean difference −1.53; 95% confidence interval −3.28; 0.21, p = 0.08). There were no studies identified assessing the role of statins in treatment of vascular dementia. There was no evidence that statins were detrimental to cognition. Conclusions There is insufficient evidence to recommend statins for the treatment of dementia. Copyright © 2012 John Wiley & Sons, Ltd.